1976
DOI: 10.1007/bf00220328
|View full text |Cite
|
Sign up to set email alerts
|

Morphological aspects of the hypothalamic-hypophyseal system

Abstract: Enzyme-histochemical methods were used to study the metabolic activity of specialized ependyma of the ventrolateral walls and floor of the third ventricle in young male and female rats during the "critical period" of sexual differentiation of the hypothalamus (one week after birth). Histochemical tests were conducted for glutamic dehydrogenase, lactic dehydrogenase, glucose-6-phosphate dehydrogenase, glycerophosphate dehydrogenase and NADH2-dehydrogenase. Enzyme activity was judged by cytospectrophotometry. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…ewe [8. 9] and hamster [19], Electron-micro scopic studies have also shown that following dexamethasone treatment tanycytes show an increase in synthesis and transport activities, especially in the floor of the third ven tricle [3], However, in adrenalectomized animals there is a decrease in synthesis and transport activities in the floor of the third ventricle. Again, plasma osmolarity changes induce cistern-like structure formation in the tanycytic cytoplasm, suggesting a receptor function [5.…”
Section: Discussionmentioning
confidence: 99%
“…ewe [8. 9] and hamster [19], Electron-micro scopic studies have also shown that following dexamethasone treatment tanycytes show an increase in synthesis and transport activities, especially in the floor of the third ven tricle [3], However, in adrenalectomized animals there is a decrease in synthesis and transport activities in the floor of the third ventricle. Again, plasma osmolarity changes induce cistern-like structure formation in the tanycytic cytoplasm, suggesting a receptor function [5.…”
Section: Discussionmentioning
confidence: 99%